Evaluation of Anti-diabetic Activity of Bambusa Bambos using Streptozocin Diabetic Model Induced - Gurjar, Vikram Singh; Sharma, Yogesh Kumar (Journal of Biomedical and Pharmaceutical Research, 2022)
Diabetes mellitus, commonly known as diabetes, is a group of metabolic disorders characterized by a high blood sugar level over a prolonged period of time. If left untreated, diabetes can cause many health complications. Acute complications can include diabetic ketoacidosis, hyperosmolar hyperglycemic state, or death. Serious long-term complications include cardiovascular disease, stroke, chronic kidney disease, foot ulcers, damage to the nerves, damage to the eyes and cognitive impairment. Herbal medicine is a drug or preparation made from plants or parts of plant (leaves, root, bark, seeds and flowers) valued for its medicinal, aromatic or savoury qualities to treat the symptoms of wide range of problems from depression to cold and flu. Herbal medicine has been widely used for thousands of years. One of them is Bambusa bambos which is very well known for its ethno pharmacological activities, also known as Bans in hindi andvansa in sanskrit. leaves were washed and dried was extracted with hydroalcohol. The present study represents the assessment of anti- hyperglycemic effects of the hydro alcoholic extract from bambusa bambos in streptozotocin (STZ) induced diabetic rats. The bambusa bambos hydoalcoholic extracts at the tested doses of 100, 200 and 400 mg/kg showed comparable activity with the standard. Metformin decreases hyperglycaemia primarily by suppressing glucose production by the liver. The streptozotocin induced diabetes is characterized by a severe loss in body weight. The decrease in the body weight of diabetic rats in this study was due to the loss or degradation of structural proteins. Insulin plays an important role in the regulation of protein synthesis and proteolysis in skeletal muscle. In the present study, diabetic control rats showed marked reduction in their body weight when compared to normal rats. The ability of the extract to protect body weight loss in diabetic rats seems to be the result of their ability to reduce hyperglycemia. During the study, it was found that the extract significantly (p<0.001) controlled the blood glucose level in STZ-induced diabetic rats. The bambusa bambos hydroalcoholic extracts showed reduction in blood glucose level in STZ-induced diabetic rats when compared to the diabetic control group at a dose of 400 mg/kg, Keywords: Bambusa bambos, Hydroalcoholic extracts, Metformin, Streptozotocin.